Heaven’s Way and Life: On the Commonalities between Jesus and Confucius's Outlook on Life - TANG, Shiwen (Journal of Research for Christianity in China (JRCC), 2024)
As great teachers, both Jesus and Confucius are concerned about Heaven’s Way and life. There are many commonalities and similarities between Jesus and Confucius’s outlook on life. They all teach people how to fear (respect) Heaven and love people, advocate the unity (harmony) of Heaven and human revere one’s father and mother, love other people as oneself, seek peace, and finally make this world become one family and one harmonious world. The teachings of Jesus and Confucius are not contradictory, but they complement each other. The Chinese inherent Confucian culture of Heaven’s Way and philosophy of life is one of the ideas closest (most closely related) to Christianity. If Chinese Confucian culture accepts the Gospel of Christ, it will undoubtedly be as stated in the Vatican II Council said, that and the result will make the content of Christian churches and Chinese culture more abundant and brighter (brilliant).
Keywords: Jesus, Confucius, outlook on life, comparative ethics, and commonalities